Seasonal Changes and Relationships in Training Loads, Neuromuscular Performance, and Recovery and Stress State in Competitive Female Soccer Players - Ishida, Ai; Bazyler, Caleb D.; Sayers, Adam L.; Stone, Michael H.; Gentles, Jeremy A. (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to examine seasonal changes in training load (TL), neuromuscular performance, subjective recovery and stress state and to investigate the relationships between acute and chronic TL and neuromuscular performance in competitive female soccer. METHODS: Nine competitive female soccer players (20.0±1.7yrs; 60.3±6.3kg; 164.0±5.8cm) completed the Short Recovery and Stress Scale and countermovement jump (CMJ) with polyvinyl chloride pipe (CMJ0) and 20kgs barbell (CMJ20) at 2-3 hours before 1st match (NC1), 6th match (NC2), 9th match (C1), and 15th match (C2) of the competitive season. TL included total distance, high speed running and PlayerLoad. Acute and chronic TL was calculated using the average of 2 days (D2), 7 days (D7), and 21 days (D21) prior to 4 match-plays. RESULTS: Significant decreases were found from NC1 to C1 in D7 total distance (p=0.03, Cohen’s effect size [dz]=1.40). D7 total distance and PlayerLoad significantly decreased from NC to C1 and C2 (p=0.001 to 0.01, dz =1.40 to 1.72). Significant increases were observed from NC1 to C1 in CMJ0 jump height (p=0.03, dz =1.40), (p=0.021, dz =1.44), and peak power (p=0.03, dz =1.32). Significant negative correlations were observed for D7 total distance and CMJ0 jump height (p=0.02, r=-0.79) and peak power (p=0.03, r=-0.71) at C2, while significant positive correlations were observed at C1 for D7 PlayerLoad and CMJ0 jump height (p=0.02, r=0.80). CONCLUSION: CMJ0 jump height and peak power may increase from pre-season to the mid competitive season. Seasonal variations may affect the relationships between D7 TL and CMJ0 performance.